Legal interpretation perspectives from other disciplines and private texts - Greenawalt, Kent, 1936- (Oxford : New York ; Oxford University Press, 2011)
This title focuses on textual interpretation of the law. All law needs to be interpreted, and there are many ways to do it. Greenawalt covers the dominant methods of legal interpretation explaining their underlying structure and efficacy.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Law -- Interpretation and construction; Law -- Philosophy; Comparative law